Nitrogen mineralization in soils receiving different rates of cattle-slurry and cropped with forage maize - Pereira, J. (2012)
The quantification and the time-course of organic nitrogen release from slurry applied at sowing of maize grown for silage is of major importance to increase the efficient use of slurry-N and to reduce environmental impacts. The objective of this work was to quantify the net N mineralization measured in the 0-30 cm soil layer during the forage maize growth period, when cattle slurry was applied at sowing to supply 340 (T1), 190 (T2) and 0 (T3) kg total N ha -1 . The experiment was carried out during 1999 in the NW region of Portugal. Net mineralization rates were significantly different and reached high values, being a relevant source of N for the plants. During the forage maize crop net mineralization represented 401, 281 and 174 Kg N ha -1 respectively on treatments T1, T2 and T3, values that correspond to average net N mineralization rates of 1.3, 0.9 and 0.6 mg N kg -1 soil day -1 . The forage maize dry matter yields on these treatments reached 22, 19 and 13 t ha -1 , respectively for T1, T2 and T3.